Adverse effects of vancomycin in children: a review of 22 cases - Reis, Amélia Gorete Afonso da Costa; Grisi, Sandra Josefina Ferraz Ellero (São Paulo Medical Journal, 1997)
Vancomycin has been frequently recommended for the treatment of multi-resistant infections.Twenty-two children undergoing vancomycin treatment were observed. Nine adverse effects were registered in 6 children: eosinophilia in 5 cases, skin rash in 2 cases, and an increase in plasma creatinine in 2 cases. All adverse effects remitted with withdrawal of the drug.